The Development of Telegram Bot Api to Maximize The Dissemination Process of Islamic Knowledge in 4.0 Era - William Santoso; Wilda Nurjannah; Mahgrisya Shudhuashar; Asyifa Tasya Fadilah; Muhammad Destamal Junas; Dini Handayani (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2022)
Information technology is developing quickly in this era as if the world is in our hands. All forms of information can be accessed quickly, including Islamic information by utilizing internet technology. One of well-known medium to spread information is social media. Telegram, as one of the social media that has various beneficial features and widely used by people, has the potential to be a medium for disseminating Islamic knowledge. To improve the dissemination process of Islamic knowledge, we used one of the services found on Telegram namely chatbot. By utilizing Telegram Bot API, we make a bot that can automatically provide output according to the command given by the user in this case, giving various Islamic knowledges that users need such as Tafsir, hadith, daily prayer, and even Islamic history with a reliable source. Based on the testing result, the bot is showing a good result because it’s displaying the expected output and all features are working fine as they should be. We hoped that this bot can maximize the dissemination process of Islamic knowledge in Indonesia and reach wider audience coverage.